COVID-19 and literature evidence: should we publish anything and everything? - Chan, Jeremy; Oo, Shwe; Chor, Cheryl Yan Ting; Yim, Daniel; Chan, Jeffrey Shi Kai; Harky, Amer (Acta Biomedica Atenei Parmensis, 2020)
COVID-19 first presented in Wuhan, Hubei Province, China in December 2019. Since then, it has rapidly spread across the world, and is now formally considered a pandemic. As of 4th of May more than 3.2 million people have been infected and over 250,000 people has died. Since the very start, scientists and researchers have tried to utilize this case to publish academic experiences and suggestions toward fighting this virus, which is lethal in some cases. To date, more than 9,000 academic papers have been published since December 2019. The quality of publications varies from a plane letter to editor to randomized studies. This review aims to analyse the current published literature related to COVID-19 and assess the quality of such articles.